The role of game riskiness on the expectation-cooperation link in social dilemmas and its relations with fear and greed - Gary Ting Tat Ng; Wing Tung Au; Derek Chun Kiu Lai (Judgment and Decision Making)
Game riskiness is an index to describe the variance of outcomes of choosing cooperation relative to that of choosing defection in prisoner’s dilemmas (PD). When the variance of cooperation is larger (smaller) than that of defection, the PD is labeled as a more-risky PD (less-risky PD). This article extends the previous work on game riskiness by examining its moderating role on the effect of expectation on cooperation under various PDs. We found across three studies that game riskiness moderated the effect of expectation on cooperation such that the effect of expectation on cooperation was larger in more-risky PDs than in less-risky counterparts. This effect was observed in N-person PD (Study 1), PD presented in both gain and loss domains (Study 2), and PD where expectation was manipulated instead of measured (Study 3). Furthermore, we found that participants cooperated more in PDs presented in the gain domain compared to those presented in the loss domain, and this effect was again moderated by game riskiness. In addition, we illustrated mathematically that game riskiness is related to other established indices of PD, including the index of cooperation, fear index, and greed index. This article identified game riskiness as a robust situational factor that can impact decisions in social dilemmas. It also provided insights into the underlying motivations of cooperation and defection under different expectations and how game riskiness can be utilized in cooperation research.